2004
DOI: 10.1111/j.1471-8286.2004.00630.x
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphic microsatellite markers for inferring diversity in wild and domesticated sugar beet (Beta vulgaris)

Abstract: Eight microsatellite loci were characterized within two cultivated beet (Beta vulgaris ssp. vulgaris) accessions and one accession of the wild progenitor of domesticated sugar beet, Beta vulgaris ssp. maritima. Allele diversity was high, yielding two to 11 alleles per locus. Polymorphism information content (PIC) values obtained for these eight loci where also high and indicate the highly informative nature of the microsatellites presented here. These described markers add to a small set of publicly available … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
1
4

Year Published

2010
2010
2018
2018

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 12 publications
3
19
1
4
Order By: Relevance
“…Development and use of molecular markers for diversity evaluation and breeding in sugar beet is relatively novel. RAPD and microsatellite markers were previously applied to sugar beet (Beta vulgaris) for germplasm identification and genome mapping (Uphoff and Wricke, 1995;Richards et al, 2004); however, only limited ISSR sugar beet data are publicly available. It is therefore of key importance that GD databases for sugar beet be extended using RAPD and ISSR markers.…”
Section: Introductionmentioning
confidence: 99%
“…Development and use of molecular markers for diversity evaluation and breeding in sugar beet is relatively novel. RAPD and microsatellite markers were previously applied to sugar beet (Beta vulgaris) for germplasm identification and genome mapping (Uphoff and Wricke, 1995;Richards et al, 2004); however, only limited ISSR sugar beet data are publicly available. It is therefore of key importance that GD databases for sugar beet be extended using RAPD and ISSR markers.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, it is believed that comparison of different marker types, i.e. arbitrary and repetitive as well as these related to specific traits, gives a more detailed insight into the direction of selection and composition of natural populations (Richards et al 2004), which in our study was also extended to commercially-produced sugar beet representatives. Due to the risks associated with disease spread in highly uniform populations, our aim was to reveal the genetic structure represented by present cultivar germplasm in relation to their wild counterparts using neutral and specific rhizomania resistance-related molecular markers.…”
Section: Discussionmentioning
confidence: 95%
“…Previously, neutral molecular markers were also broadly employed for characterization of Beta and Patellifolia genetic resources (Reamon-Büttner et al 1996; Kubis et al 1997;Smulders et al 2010). These techniques allowed precise assessment of the genetic diversity existing in cultivated and wild beet relatives and suggested that a considerable pool of alleles was lost during the domestication process as compared to wild sea beets which probably bear more resemblance to sugar beet ancestors, eventually leaving as low as one third to one fourth of the available natural variation (Richards et al 2004;Fénart et al 2008;Saccomani et al 2009;Biancardi et al 2010). Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Ispitivanjem genetičke divergentnosti između velikog broja genotipova šećerne repe uz pomoć SSR i SRAP markera bavili su se Wang et al (2008), Li et al (2010), Wang et al (2011). Mikrosatelitski markeri predstavljaju moćan alat za procenu genetičke divergentnosti i ocenu strukture populacije šećerne repe (Richards et al, 2004).…”
Section: Dnk Markeri U Oplemenjivanju šEćerne Repeunclassified
“…U pogledu broja alela po lokusu ova istraživanja su u skladu sa istraživanjima Smulders et al, (2010).Oni su u svom istraživanju korišćenjem 25 SSR markera po lokusu umnažali između 1,95 i 3,74 efektivna alela. Prema istraživanju Richards et al, (2004), koji su ispitivali tri populacije šećerne repe, broj umnoženih alela po lokusu se kretao od 2 do 11, visoke heterozigotnosti i indeksa polimorfne informacije. Rezultatima iz ovog istraživanja potvrđene su vrednosti u pogledu broja alela, heterozigotnosti i indeksa polimorfne informacije za ispitivane zajedničke mikrosatelite.U istraživanjima Simko et al, (2012) broj alela po lokusu se kretao od 2 do 9, sa prosekom od 4,3, pri čemu je PIC vrednost iznosila čak 0,59.…”
Section: Molekularne Analizeunclassified